Medical Interns’ Knowledge, Attitude, and Practice Toward People Living with HIV: Multicenter Experience from Saudi Arabia - Malli, Israa Abdullah; Hamdan, Dalia; Aljahdali, Alhanoof; Almutairi, Amal; Jar, Raghad; Alzahrani, Reham; Khan, Muhammad Anwar (HIV/AIDS (Auckland), 2023)
Background: Discrimination by some healthcare providers toward people living with HIV/AIDS has been documented. Differences in cultural backgrounds make it harder for future doctors, who need a lot of knowledge and a positive attitude to treat patients. In conservative countries like Saudi Arabia, not enough is known about how much medical interns know about HIV and how they feel about people living with HIV/AIDS. Methods: From April to September 2021, this cross-sectional study use non-probability random sampling and utilized a self-administered questionnaire to collected the data from 346 medical interns who had graduated from five different medical schools. Results: Most of the subjects correctly identified the main transmission routes, such as unprotected sex (94.57%), blood and body fluid exchange (94.19%), and sharing needles or syringes (91.47%). But they did not know what the most common co-infections were for HIV patients or how to protect themselves after exposure. This paper showed that medical interns have some stigmatizing behaviors toward patients living with HIV, as 31.1% and 22.9% agreed, respectively, that they would feel more sympathetic toward people who get AIDS from blood transfusions compared to IV drug users (IDU). Conclusion: Medical interns also showed some positive attitudes, as more than half of the sample (56.2%) would not isolate beds for people living with HIV/AIDS. The study's conclusion is that HIV education and training programs should be added for medical interns, which might have a significant positive impact on their attitude. Keywords: people living with HIV/AIDS, AIDS, medical, interns, knowledge, attitude, HIV, PLWHA